Methods in microbiology. - Williams, Peter, 1945 December 20-; Ketley, Julian M.; Salmond, George (Methods in microbiology, 1998)
Established almost 30 years ago, Methods in Microbiology is the most prestigious series devoted to techniques and methodology in the field. Now totally revamped, revitalized, with a new format and expanded scope, Methods in Microbiology will continue to provide you with tried and tested, cutting-edge protocols to directly benefit your research. Key Features * Focuses on the methods most useful for the microbiologist interested in the way in which bacteria cause disease * Includes section devoted to 'Approaches to characterising pathogenic mechanisms' by Stanley Falkow * Covers safety aspects, detection, identification and speciation * Includes techniques for the study of host interactions and reactions in animals and plants * Describes biochemical and molecular genetic approaches * Essential methods for gene expression and analysis * Covers strategies and problems for disease control.